REVIEW OF MAQASHID SYARIAH AND BANGKALAN ULAMA ON HALAL CERTIFICATION OBLIGATIONS - Ila Safila; Hammam (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
In Indonesia, especially the Bangkalan regency area where the majority of the population is Muslim. Therefore, products consumed must be halal certified in accordance with Islamic law in order to be applied properly and provide comfort and tranquility for Muslims. Considering that the Bangkalan area is an area whose religion is still very thick, so it is very unfortunate if the community is indifferent to the obligation of halal certification. Therefore, the people of Bangkalan must pay attention to product demand. One way to pay attention to the products consumed is to guarantee halal certification. From the statement listed above, the researcher wants to raise the "Review of Sharia Maqashid and Bangkalan Ulama on the Obligation of Halal Certification". Researchers will review more deeply the obligation of halal certification according to the ulama bangkalan perspective of maqashid sharia. The research method that researchers want to use is the qualitative descriptive method.